Second generation Monitoring of Pixel System (MOPS) chip for the Detector Control System (DCS) of the ATLAS ITk Pixel detector. (1st April 2023) - Ahmad, R.; Adam, A.; Besproswanny, J.; Karagounis, M.; Kind, P.; Kersten, S.; Qamesh, A.; Walsemann, A.; Zeitnitz, C.
Abstract: The MOPSv2 chip is an Application Specific Integrated Circuit (ASIC) to provide the temperature and the voltage monitoring data of individual front-end detector modules to the DCS of the ATLAS ITk Pixel detector. The chip implements CANopen in a hardwired logic, provides the possibility of remote reset without a power cycle and automated on-chip frequency trimming using CAN messages. The chip has proven to be radiation hard during testing up to an ionizing dose of 500 Mrad, immune to Single Event Upsets (SEUs) and works reliably under irradiation at high operating temperatures of up to 40 °C. In this paper, the functionality and performance of the second version of the chip will be discussed, and also results from the irradiation campaigns will be presented.